Water consumption in pediatrics - Rodríguez Weber Miguel Ángel; Arredondo García José Luis; García de la Puente Silvestre (Instituto Nacional de Pediatría, 2014)
Special considerations must be taken to calculate water require- ments of newborns and breastfeeding children; however, all their water needs should be covered with breast milk or breast-milk substitute formula. There is a need for 100 mL of water per 100 kcal consumed, or of 1,800 mL per square meter body surface area. From the age of six months, it is advisable to start providing 30 to 60 mL of water per day, with progressive increase; before that age, any other liquid must be avoided. Inadequate preparation of a substitute formula may cause hydric intoxication, or infections if the water used is contaminated. The increase in obesity and overweight is the result of increased intake of sugary beverages in children. This increased intake can also be linked to diabetes and other physiological and cognitive problems. Mexican children and teenagers have increased their caloric intake from sugary beverages in 126% between 1999 and 2006. As one of many healthy habits that children must acquire from home, is the avoi- dance of sugary beverages and the acknowledgment of water as a preferred hydration source.